THE IMPACT OF PHYSICAL ACTIVITY ON BOWEL PERISTALSIS - Wiktoria Łobodzińska; Wojciech Gawęda; Maciej Ficek; Justyna Adamczyk; Zuzanna Hamouta (International Journal of Innovative Technologies in Social Science, 2025)
Purpose: The aim of this article is to analyze the available scientific evidence regarding the impact of physical activity on intestinal peristalsis, with a particular focus on the physiological mechanisms underlying this process. The article seeks to assess the role of regular physical exercise in improving bowel motility, reducing constipation, and promoting overall gastrointestinal health, as well as understanding the potential mechanisms linking physical activity to enhanced intestinal peristalsis." Methodology: A systematic review of RCTs and meta-analyses from PubMed (since 2015) was conducted. Studies on various PA interventions, combined diet/exercise effects, and specific populations (IBS, older adults) were included. Findings: Meta-analyses show PA (moderate/high, aerobic) significantly reduces constipation risk (RR 1.97, 0.69) and improves symptoms. PA enhances colonic motility, reduces transit time, and modulates gut microbiota. Synergistic with diet. Benefits IBS. Conclusions: Physical activity, especially moderate aerobic exercise, consistently benefits bowel peristalsis and alleviates constipation by improving motility, transit time, and gut microbiota. It’s a valuable non-pharmacological intervention.